Sequence variation of latent membrane protein 2A (LMP2A)gene from Epstein-Barr virus epitope cytotoxic T-lymphocyte (CTL)related to human leucocyte antigen-A24 (HLA-A24)in peripheral blood sample and cytobrushof nasopharyngeal cancer patients - Maya Esther Wullur Moningka; Agus Surono; Sofia Mubarika (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Epstein-Barr virus (EBV) infects lymphocyte B and triggers latent phase in the host so that it causes nasopharyngeal carcinoma (NPC). Latent membraneprotein 2A (LMP2A) epitope CTL-HLA-A24 is a target for recognition by cytotoxic T lymphocyte(CTL). The change in the epitope could influence the latency of particular EBV in the host due toits ability to evade immune surveillance mediated by CTL. The study aimed to determine thesequence variation of LMP2A epitope CTL-HLA-A24 gene from the peripheral blood samples and cytobrush of the NPC patients. Case-series study was conducted with total 16 cytobrush samples from NPC patients. DNA isolation, polymerasechain reaction (PCR) and gene sequencing were performed in this study. From cytobrush samples of NPC patients, it was found the changes of base sequence variation of LMP2A gene from GGC>GGA, CCA>CCC, TGC>TCC, GGT>GGC and TCT>ACT. CCA>CCC and TGC>TCC variations were found in epitope associated with HLA-A2 where there was a change of epitope sequence from TYGPVFMCL to TYGPVFMSL caused by missense mutation. The change of base sequence caused amino acid alteration from cysteine to serine. Whereas the variation of CCA>CCC did not change the sequence of amino acid proline so that the epitopewas unaffected. In epitope associated HLA-A2 (CLGGLLTMV), there was a change in base sequence from GGT to GGC, but there was no changes in amino acid and still as glycine. There were some new variations: in the upstream sequence of LMP2A from GGC>GGA which is silent mutation and the other variation is in downstream sequence of LMP2A from TCT>ACT which is missense mutation. Thesequence variations of LMP2A gene found in this research were GGC>GGA, CCA>CCC, TGC>TCC, GGT>GGC and TCT>ACT. In our research, we found another variation compared the previous research. The variation was in the upstream sequence of LMP2A from GGC>GGA which is silent mutation and the other variation is in the downstream sequence of LMP2A from TCT>ACT which is missense mutation.